Fracture characterization of glass fiber composite laminate under experimental biaxial loading. (15th March 2016) - Rashedi, A.; Sridhar, I.; Tseng, K.J.
Abstract: This study proposes a mixed-mode fracture criterion for glass fiber reinforced composite laminates based on numerical and experimental biaxial loading. An optimal cruciform geometry is introduced first based on finite element (FE) simulation. Characterization testing is performed successively on uniaxial and cruciform specimens to determine equivalent loaded area, notch sensitivity behavior and critical fracture toughness properties of cross-ply GFRP laminates. In experimental biaxial testing, two types of crack orientations (0°, 45°) are studied with varying crack lengths. The experimental failure points show that cross-ply GFRP laminates attain higher load bearing capability under biaxial tensile–tensile loading compared to uniaxial testing. Appropriate non-dimensional geometry factor relevant to cruciform shape is determined based on experimental data points and FE simulation. Eventually, a mixed-mode fracture criterion is proposed for cross-ply composite laminate based on the findings from biaxial experimental loading.